A NEW METHOD FOR IDENTIFYING THE ORIGINS OF SIMPLE AND COMPLEX HOPANOIDS IN SEDIMENTARY MATERIALS USING STABLE ISOTOPE LABELLING WITH 13CH4 AND COMPOUND SPECIFIC STABLE ISOTOPE ANALYSES - Crossman Z.M.; McNamara N.; Parekh N.; Ineson P.; Evershed R.P. (My University, 2001)
Forest soils were taken and incubated with 13C-labelled methane. The lipids from these soils were isolated using a Bligh Dyer extraction and fractionated. Simple hopanoids were present in the neutral fraction, while periodic acid/sodium borohydride treatment of the total lipid extract released primary alcohols from polyfunctionalised bacteriohopane derivatives. All hopanoids were analysed by GC, GC/MS and GC/C/IRMS. Specific hopanoids, namely: diploptene, 17β(H), 21β(H)-homohopanol and 17β(H), 21β(H)-bishomohopanol produced by methane oxidising bacteria were significantly enriched in 13C whilst others showed no enrichment.
Keywords: PENTACYCLIC TRITERPENOID; HOPANOID; METHANOTROPHIC BACTERIA; 13C-LABELLED METHANE; GAS CHROMATOGRAPHY/COMBUSTION/ISOTOPE RATIO MASS SPECTROMETRY (GC/C/IRMS)